Evaluating the outcomes of sublingual and vaginal misoprostol for labor induction - Bhati, Bijal; Patel, Alpesh; Gori, Mahejbin; Rana, Vaidehi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: To evaluate and compare the effectiveness, safety, and outcomes of 25 µg sublingual versus 25 µg vaginal misoprostol used for induction of labor at term. Methods: This retrospective observational study was conducted from May 2021 to October 2022. To analysed the records of 200 antenatal patients who were in their third trimester, specifically beyond 37 weeks of gestation. The study identified case files of patients who received induction of labor through sublingual versus vaginal misoprostol for various indications. The data collection process involved a thorough examination of the case record form, capturing essential details such as patients age, parity, clinical presentations, examination findings, and results from clinical assessments and ultrasonography. Additionally, it included pre-induction CTG readings, Bishop scores, the method of administering tablet misoprostol, the quantity of tablets utilized, modes of delivery, fetal and maternal outcomes, any complications encountered, and NICU admissions. Results: Vaginal delivery occurred in 90% of the vaginal group and 88% of the sublingual group. The mean induction-to-delivery interval was slightly shorter in the vaginal group. Oxytocin augmentation was more frequently required with sublingual misoprostol. Adverse effects such as fever, nausea, and diarrhea were occurring slightly more in the sublingual group without statistical significance. Non-reassuring cardiotocography was the leading indication for caesarean section. Neonatal outcomes showed no significant difference. Conclusions: Both sublingual and vaginal misoprostol are equally effective and safe for term induction. The route may be individualized according to patient preference and clinical suitability.